Analysis of Marketing Strategies through Endorsements in Building Brand Awareness from the Perspective of Islamic Business Ethics - Ulfa, Sania Maria; Amir, Siib; Ardyansyah, Farid (Imara: Jurnal Riset Ekonomi Islam, 2024)
Background. The rise of promotions through endorsements to build brand awareness has led celebrity endorsers to become less cautious in promoting products on social media. Therefore, it is important for business owners to consider the criteria for promoters in accordance with Islamic business ethics principles.Purpose. This study aims to analyze marketing strategies through endorsements to build brand awareness and review them in the context of Islamic business ethics. Specifically, the research was conducted on a business in the furniture sector, namely May Be Mebell, Bangkalan.Method. A descriptive qualitative approach was used, with data obtained from field observation notes and interviews with the owner, content viewers, and customers of May Be Mebell. Data analysis was conducted through the stages of data reduction, presentation, and verification.Results. The research findings indicate that May Be Mebell’s marketing strategy, which involves active content marketing and collaboration with celebrity endorsers, has successfully built brand awareness and increased sales volume. The endorsement strategy employed also aligns with Islamic business ethics principles. However, special attention is needed regarding the principle of trustworthiness, as the endorsers are perceived to be overly enthusiastic in promoting the products.Conclusion. This study has significant implications for endorsement practices in efforts to build brand awareness. By understanding the appropriate criteria for endorsers, business owners can align their approach with Islamic business ethics principles to achieve their goals.